2000
DOI: 10.1034/j.1600-0722.2000.108003222.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of non‐collagenous dentin matrix proteins and proteoglycans, and their relation to calcium accumulation in bisphosphonate‐affected rat incisors

Abstract: It has been reported that multiple injections of 1-hydroxyethylidene- 1,1-bisphosphonate (HEBP) to rats prevent mineralization of incisor dentin, thereby revealing high concentrations of calcium in the non-mineralized matrix of circumpulpal dentin. To identify the molecules responsible for calcium accumulation in circumpulpal dentin matrix, rats were injected daily with HEBP (8 mg P/kg) for 7 d, and the incisors processed for various histochemical and immunohistochemical staining of non-collagenous matrices of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
3
3
0
3
Order By: Relevance
“…In total, these dentin changes suggest a role for OPN in regulating the pace of dentinogenesis and influencing the extent of tissue mineralization. This is consistent with previous studies that supported a role for ECM phosphoproteins in directing circumpulpal dentin mineralization [67–69], or demonstrated OPN interaction with matrix vesicles in mantle dentin [6,27]. Moreover, these observations of OPN effects on dentin are supportive of findings pointing to increased OPN deposition in pathologies of dentin hypomineralization, e.g.…”
Section: Discussionsupporting
confidence: 92%
“…In total, these dentin changes suggest a role for OPN in regulating the pace of dentinogenesis and influencing the extent of tissue mineralization. This is consistent with previous studies that supported a role for ECM phosphoproteins in directing circumpulpal dentin mineralization [67–69], or demonstrated OPN interaction with matrix vesicles in mantle dentin [6,27]. Moreover, these observations of OPN effects on dentin are supportive of findings pointing to increased OPN deposition in pathologies of dentin hypomineralization, e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings have been obtained in rat incisors (Ohma et al 2002) and molars (Sasano et al 2001;Hosoya et al 2003). Tadatomo et al (2002) and Matias et al (2003b) have also presented micrographs in which dentin is almost completely immuno-negative for BSP in rat molars.…”
Section: Discussionsupporting
confidence: 83%
“…Following an examination of previous light-microscopic studies, we have found that studies supporting our findings involve the use of buffered-paraformaldehyde for fixation and EDTA for demineralization (Sasano et al 2001;Ohma et al 2002;Tadatomo et al 2002;Hosoya et al 2003), whereas most other studies employ other chemicals: 95% ethanol (Somerman et al 1990b), Bouin's fixative (MacNeil et al 1994(MacNeil et al , 1995b, and 10% formalin (Ivanovski et al 2001) for fixation; acetic acid (MacNeil et al 1994(MacNeil et al , 1995b and 0.2N HCl (Chen et al 1993;Lekic et al 1996aLekic et al , 1996b for demineralization. Bufferedparaformaldehyde and EDTA are generally recommended for the immunohistochemistry of mineralized tissue, because different chemicals often cause unstable and misleading immunoreactions.…”
Section: Discussionsupporting
confidence: 55%
“…Notably, circumpulpal dentin formation has been described as depending on other ECM proteins, including related SIBLING family members DMP1, DSP, and DPP (Bleicher et al, 1999; Gibson et al, 2013c; Lu et al, 2007; Ohma et al, 2000; Sreenath et al, 2003; Steinfort et al, 1989; Steinfort et al, 1990; Ye et al, 2004). Like BSP, these multifunctional SIBLINGs can both directly and indirectly affect mineralization, and may also be involved in cell signaling and differentiation, and other local or systemic effects (Gericke et al, 2010; Gibson et al, 2013a; He et al, 2003; Hunter et al, 1996; Siyam et al, 2012; Tartaix et al, 2004).…”
Section: Discussionmentioning
confidence: 99%